Genistein inhibits Ca2+ influx and glutamate release from hippocampal synaptosomes: putative non-specific effects - Pereira, Daniela B. (2003)
The role of protein tyrosine kinases on glutamate release was investigated by determining the effect of broad range inhibitors of tyrosine kinases on the release of glutamate from rat hippocampal synaptosomes. We found that lavendustin A and herbimycin A did not inhibit glutamate release stimulated by 15 mM KCl, but genistein, also a broad range inhibitor of tyrosine kinases did inhibit the intracellular Ca2+ concentration response to KCl and, concomitantly, decreased glutamate release evoked by the same stimulus, in a dose-dependent manner. These effects were not observed with the inactive analogue genistin. Therefore, we investigated the mechanism whereby genistein modulates Ca2+ influx and glutamate release. Studies with voltage-gated Ca2+ channel inhibitors showed that [omega]-conotoxin GVIA did not further inhibit glutamate release or the Ca2+ influx stimulated by KCl in the presence of genistein. This tyrosine kinase inhibitor and [omega]-agatoxin IVA had a partially additive effect on those events. Nitrendipine did not reduce significantly the KCl-induced responses. Genistein further reduced Ca2+ influx in response to KCl in the presence of nitrendipine, [omega]-conotoxin GVIA and [omega]-agatoxin IVA, simultaneously. The effect of tyrosine phosphatase inhibitors was also tested on the influx of Ca2+ and on glutamate release stimulated by KCl-depolarization. We found that the broad range inhibitors sodium orthovanadate and dephostatin did not significantly affect these KCl-evoked events.